PERSEPSI MASYARAKAT MENGENAI PEMBANGUNAN FISIK MENGATASI PERMASALAHAN BANJIR KELURAHAN SUNGAI PINANG DALAM KOTA SAMARINDA - Muhammad Habibi; Arbainah Saidi (ITB AAS Indonesia Surakarta, 2023)
The purpose of this study was to find out the public's perceptions and the underlying ideas regarding physical development to overcome flood problems in Sungai Pinang Dalam Village, Samarinda City. The results of the study show that the community members give their perception that from year to year there has been no change, even though Probebaya has existed. Physical development under the pretext of drainage arrangements and others, in fact only moved the flood point from one point to another. Flood management by the City Government of Samarinda has not been consistent, not integrated, not integrated and not systematic. According to the public's perception, the arrangement should have started from the SKM estuary on the Mahakam River and then moved towards the outskirts and the border of Samarinda City and the Kutai Kartanegara region, both to the north, west, south and east. Furthermore, the basis for people's perceptions in physical development to overcome flooding in Samarinda City is based on a simple understanding, that the laws of physics where water flows from high areas to low areas. Likewise, if the flow of water is blocked or blocked, or due to space narrowing and siltation, it will cause water to overflow and flow in an unspecified and unpredictable direction, in addition to causing inundation within a certain period of time and even quite a long time, which causes flooding.